Et2NH catalysis-enabled construction of convolutamydine A-fused morusignin L-scaffolds and their biological evaluation for anticancer activities. Issue 6 (19th March 2017) - Lin, Bing; Lu, Yi; Huang, Jun-Fei; Gong, Yi; Liu, Huan-Huan; Liu, Xiong-Li; Tian, Min-Yi; Zhou, Ying; Yuan, Wei-Cheng
ABSTRACT: Described herein is a facile and efficient methodology toward the synthesis of novel convolutamydine A-incorporated morusignin L scaffold3 from an aldol addition event of carbonyl compounds to isatins through enamine catalysis. Products featuring a quaternary carbon center were smoothly obtained in good yields (up to 85% yield). This protocol also represents the first construction of flavonoid skeleton-fused oxindole molecules, thus leading to new knowledge in the fields of both molecular complexity and diversity synthesis and the lead compound discovery. Furthermore, their biological activities against human prostate cancer cells PC-3 and human leukemia cells K562 have been preliminarily demonstrated by in vitro assays. The results demonstrated that most of these compounds obtained by this protocol showed comparable or even much better activity than the positive control of cisplatin. GRAPHICAL ABSTRACT: